Pomegranate extract mechanism in inhibiting the development of oral cancer: A review - Imanu, Sherina Fatwa; Leginis, Shinadilla Naza; Iqbal, Mohammad; Surboyo, Meircurius Dwi Condro (Indonesian Journal of Dental Medicine, 2023)
Background: Oral cancer is one of the most aggressive and invasive cancers with high metastatic potential. Oral cancer is cancer with the 11th highest number of cases in the world. Oral cancer is treated with chemotherapy and radiotherapy. However, this therapy causes side effects in the form of damage to normal cells in the surrounding tissue. Pomegranate extract contains polyphenols which may be great for inhibiting the development of oral cancer. Purpose: This article presents a systematic and comprehensive review of the potential of pomegranate extract as a natural product to inhibit the development of oral cancer. Review: Pomegranate extract was obtained by ethanol extraction using maceration method. The main content of pomegranate is polyphenolic compounds such as punicalagin, tannins, flavonoids, and ellagic acid. This compound reduces ATP formation, shortens the subG1 phase, and increases apoptosis. At the microcellular level, pomegranate extract can inhibit the activity of MMP-2 or MMP-9 to produce anti-proliferative, anti-angiogenesis and pro-apoptotic processes of cancer cells at concentrations of 25 and 50 Î¼g/ml. Anti-proliferative and pro-apoptotic effects are produced through mitochondrial damage mechanisms. Exposure after 72 hours can reduce oral cell viability greater than exposure after 24 hours. Conclusion: Pomegranate extract is likely has four mechanisms to oral cancer: inhibiting the invasion, migration and growth of oral cancer cells, increasing oral cancer cell apoptosis and regulating antioxidant genes. So that this material can be used as a candidate for oral cancer therapy.